INTEROPERABILITY MATTER: LEVELS OF DATA SHARING, STARTING FROM A 3D INFORMATION MODELLING - Tommasi, C.; Achille, C. (International archives of the photogrammetry, remote sensing and spatial information sciences., 2017)
Nowadays, the adoption of BIM processes in the AEC (Architecture, Engineering and Construction) industry means to be oriented towards synergistic workflows, based on informative instruments capable of realizing the virtual model of the building. The target of this article is to speak about the interoperability matter, approaching the subject through a theoretical part and also a practice example, in order to show how these notions are applicable in real situations. In particular, the case study analysed belongs to the Cultural Heritage field, where it is possible to find some difficulties – both in the modelling and sharing phases – due to the complexity of shapes and elements. Focusing on the interoperability between different software, the questions are: What and how many kind of information can I share? Given that this process leads also to a standardization of the modelled parts, is there the possibility of an accuracy loss?